Enantioselective Total Synthesis of 3β‐Hydroxy‐7β‐kemp‐8(9)‐en‐6‐one, a Diterpene Isolated from Higher Termites. Issue 50 (15th November 2017) - Wang, Yuzhou; Jäger, Anne; Gruner, Margit; Lübken, Tilo; Metz, Peter
Abstract: The first total synthesis of the title diterpene was accomplished starting from the Wieland–Miescher ketone. A diastereoselective sulfa‐Michael addition enabled the generation of the delicate β, γ‐unsaturated ketone moiety, while the tetracyclic kempane skeleton was readily constructed through domino metathesis. Abstract : Sulfur helps ! The first total synthesis of the title diterpene was accomplished starting from the Wieland–Miescher ketone. A diastereoselective sulfa‐Michael addition enabled the generation of the delicate β, γ‐unsaturated ketone moiety, while the tetracyclic kempane skeleton was readily constructed through domino metathesis.